Prevention of radial artery occlusion with rivaroxaban after trans-radial access coronary procedures: The RIVARAD multicentric randomized trial - Hammami, Rania; Abid, Slim; Jihen, Jdidi; Triki, Zied; Ben Mrad, Imtinene; Kammoun, Amine; Slim, Mehdi; Kacem, Marwen; Thabet, Houssem; Abdessalem, Aymen Ben; Mallek, Souad; Charfeddine, Selma; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background Radial artery occlusion (RAO) remains the most frequent complication of trans-radial access. Once the radial artery is occluded, its future use as an access site for coronary procedures, or as a conduit for coronary bypass grafting or fistula for hemodialysis, will be precluded. Therefore, we aimed to assess the value of the short-term use of Rivaroxaban to prevent RAO after a trans-radial coronary procedure. Methods This was a prospective, open-label, randomized study. The patients were randomly assigned (1:1) to one of two groups: those who received Rivaroxaban 10 mg for 7 days following the trans-radial coronary procedure (the Rivaroxaban Group) and those who received the standard treatment (the Control Group). The primary outcome was an occurrence of RAO evaluated by Doppler ultrasound at 30 days, and the secondary outcomes were hemorrhagic complications according to BARC classification. Results We included 521 patients randomized into two Groups: the Control Group (N = 262) and the Rivaroxaban Group (N = 259). The 1-month RAO was significantly reduced in the Rivaroxaban Group as compared to the Control Group [6.9% vs. 13%; p = 0.011, OR = 0.5, (95% CI, 0.27–0.91)]. We noted no cases of severe bleeding events (BARC3-5). The overall incidence of minor bleeding (BARC1) was 2.3%, with no significant difference between the two groups [Rivaroxaban Group = 2.7%, Control Group = 1.9%, p = 0.54, OR= 1.4, (95%CI 0.44–4.5)]. Conclusions Short-term postoperative anticoagulation with Rivaroxaban 10 mg for seven days reduces the rate of 1-month RAO.